Exploring the Factors Influencing Donation Behavior Among the Muslim Community at LAZISNU, East Java, Indonesia - Lahuri, Setiawan bin; Mabarroh, Indah Taqiyyah; Zuhroh, Ainun Amalia; Affandi, Muhammad Taufiq (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2025)
Purpose:This study aims to identify and analyze the key factors influencing donation behavior within the LAZISNU program in East Java, Indonesia. By focusing on empirical evidence, the research seeks to contribute theoretically to the broader understanding of Islamic philanthropic behavior, particularly in the context of Indonesia’s cultural and religious diversity. The findings are also expected to inform future strategies for enhancing sustainable donor engagement within Islamic philanthropic institutions.Design/Methodology:The research method used was descriptive quantitative. The sampling technique used was random sampling with respondents from the donors LAZISNU program in East Java, totaling 399 respondents. The data analysis and hypothesis testing method uses Smart PLS 4.0 software to describe latent variables. Inner model testing through R Square (R2) 0.67 as substantial, F-Square (F2) 0.15 has a moderate effect, Q-Square (Q2) exceeds zero (0) has a good predictive relevance value, and Goodness of Fit (GoF) analysis.Findings:The findings indicate that variables such as generosity, religiosity, the influence of religious leaders, and trust in implementing institutions have a positive effect on donation behavior, as evidenced by t-statistic values greater than 1.96 and p-values less than 0.05. In contrast, income and financial security do not exhibit a significant positive effect, as indicated by t-statistic values below 1.96 and p-values greater than 0.05. Nonetheless, reporting these non-significant variables remains important, as it provides a comprehensive understanding of the tested model and highlights potential contextual or mediating factors that may influence their effects in different settings or populations.Practical Implications:This means that generosity, religiosity, the influence of religious leaders, and trust in implementing institutions in this study are the most influential on the donation behavior in LAZISNU program in East Java.Originality/Value:Specifically discuss the behavior of donating through alms management institutions by income level, generosity, financial security, and religiosity